2012
DOI: 10.1002/uog.11137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different sites of measurement for transabdominal uterine artery Doppler velocimetry at 11–13 weeks

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
3
21
0
1
Order By: Relevance
“…They reported the PI measurements were higher at site A than at site B for both the right and left uterine arteries, which is similar to the findings of this study; however, the magnitude of the difference was not reported [21]. No other studies were found that either compared different sampling sites for the uterine arteries in the first trimester or reported results for a sampling site other than the level of the internal cervical os.…”
Section: Discussionsupporting
confidence: 62%
“…They reported the PI measurements were higher at site A than at site B for both the right and left uterine arteries, which is similar to the findings of this study; however, the magnitude of the difference was not reported [21]. No other studies were found that either compared different sampling sites for the uterine arteries in the first trimester or reported results for a sampling site other than the level of the internal cervical os.…”
Section: Discussionsupporting
confidence: 62%
“…These physiological changes convert the spiral arteries from narrow muscular vessels to wide non-muscular channels independent of maternal vasomotor control. In placental dysfunction there is impaired trophoblastic invasion of spiral arteries and this impairment is most marked in PE and IUGR [6,7]. Indirect evidence of impaired placental perfusion in pregnancies destined to develop PE and IUGR has been provided by Doppler studies of the uterine arteries which showed increased PI during both the second and also in the first trimester of pregnancy [8].…”
Section: Discussionmentioning
confidence: 99%
“…The first‐trimester uterine artery PI is typically assessed by abdominal Doppler ultrasound (US) at the level of the ascending branch near the internal cervical os . The reproducibility of the technique is moderate and could potentially be improved by using transvaginal US .…”
mentioning
confidence: 99%
“…[16][17][18][19][20] The first-trimester uterine artery PI is typically assessed by abdominal Doppler ultrasound (US) at the level of the ascending branch near the internal cervical os. 8,[21][22][23] The reproducibility of the technique is moderate and could potentially be improved by using transvaginal US. 24 However, there is a controversy regarding the similarity of uterine artery PI values between the two approaches.…”
mentioning
confidence: 99%